Republic of Tajikistan : Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
The Poverty Reduction Strategy Paper discusses socioeconomic development in the Republic of Tajikistan. Although poverty reduction in rural areas is proceeding at a faster pace than in urban areas, poverty continues to be a predominantly rural phenomenon. In addition to improving the gender equality situation, there are still pressing issues related to equal access for men and women to education and land use, to the decision-making process, and to employment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet